New simulations of accreting DA white dwarfs: Inferring accretion rates from the surface contamination - Wachlin, Felipe Carlos (2022)
Context. A non-negligible fraction of white dwarf stars show the presence of heavy elements in their atmospheres. The most accepted explanation for this contamination is the accretion of material coming from tidally disrupted planetesimals, which forms a debris disk around the star. Aims. We provide a grid of models for hydrogen-rich white dwarfs accreting heavy material. We sweep a 3D parameter space that has different effective temperatures, envelope hydrogen contents, and accretion rates. The grid is appropriate for determining accretion rates in white dwarfs that show the presence of heavy elements. Methods. Full evolutionary calculations of accreting white dwarfs were computed including all relevant physical processes, particularly the fingering (thermohaline) convection, a process neglected in most previous works, which has to be considered to obtain realistic estimations. Accretion is treated as a continuous process, and bulk-Earth composition is assumed for the accreted material. Results. We obtain final (stationary or near-stationary) and reliable abundances for a grid of models that represent hydrogen-rich white dwarfs of different effective temperatures and hydrogen contents, which we apply to various accretion rates. Conclusions. Our results provide estimates of accretion rates, accounting for thermohaline mixing, to be used for further studies on evolved planetary systems.